Properties of some azo-copolyimide thin films used in the formation of photoinduced surface relief gratings. Issue 14 (19th February 2015) - Sava, Ion; Burescu, Ada; Stoica, Iuliana; Musteata, Valentina; Cristea, Mariana; Mihaila, Ilarion; Pohoata, Valentin; Topala, Ionut
<x xml:space="preserve">Abstract</x> The patterning of the free standing azo-copolyimide films under different irradiation conditions led to the uniform surface relief gratings.